Premorbid use of selective beta-blockers improves sepsis incidence and course: Human cohort and animal model studies - Hong, Shiao-Ya; Lai, Chih-Cheng; Teng, Nai-Chi; Chen, Chao-Hsien; Hsu, Chun-Chun; Chan, Nai-Ju; Wang, Cheng-Yi; Wang, Ya-Hui; Lin, You Shuei; Chen, Likwang (Frontiers in Medicine, 2023)
Introduction: Beta-blockers are widely prescribed to manage hypertension and cardiovascular diseases and have been suggested as an attractive therapy to improve the prognosis of sepsis. Herein, we investigated the potential benefits of premorbid selective beta-blocker use in sepsis with a real-world database and explored the underlying mechanism by in vivo and in vitro experiments. Methods: A total of 64,070 sepsis patients and 64,070 matched controls who were prescribed at least one anti-hypertensive drug for more than 300 days within one year were selected for the nested case-control study. Female C57BL/6J mice and THP-1 cells stimulated with lipopolysaccharide (LPS) were used for studying systemic responses during sepsis to validate our clinical findings. Results: The risk of sepsis was lower in current selective beta-blocker users than in non-users (adjusted OR (aOR), 0.842; 95% CI, 0.755–0.939), and in recent users than in non-users (aOR, 0.773; 95% CI, 0.737–0.810). A mean daily dose of ≥ 0.5 DDD was associated with a lower risk of sepsis (aOR, 0.7; 95% CI, 0.676–0.725). Metoprolol, atenolol, and bisoprolol users had lower risk of sepsis than non-users. In a LPS-induced sepsis mouse model, mice pre-fed with atenolol had significantly reduced mortality. While atenolol had some mild effects on LPS-induced release of inflammatory cytokines in septic mice, it significantly reduced serum soluble PD-L1 levels. Notably, atenolol treatment reversed the negative correlation of sPD-L1 with inflammatory cytokines in septic mice. Moreover, atenolol markedly downregulated the PD-L1 expression on LPS-stimulated THP-1 monocytes/macrophages via targeting ROS-induced NF-κB and STAT3 activation. Conclusion: Atenolol pretreatment can reduce sepsis mortality in mice, and in vivo and in vitro studies of PD-L1 expression suggest a role for atenolol in the modulation of immune homeostasis. These findings may contribute to the reduced incidence of sepsis in hypertensive patients with premorbid treatment with selective beta-blockers, especially atenolol.